Whole-farm modeling approach to evaluate different crop rotations in organic dairy systems - Abreu, Daniel Carneiro de (Universidade Federal de Viçosa, 2014)
The market for high-quality organic bread wheat (Triticum aestivum L.) is increasing in New England. This economic niche represents one alternative income for organic dairy producers (if they include wheat in their crop rotation) to supply this market by raising wheat as a cash crop. Our objective was to determine the sustainability to eight crop rotation sequences of 3-yr rotations in a long-term (25-yr) well-managed organic dairy farm. A medium-sized organic dairy farm was simulated with the Integrated Farm System Model (IFSM, version 3.6) to evaluate crop rotation (management) effects on crop performance, environmental impacts and profitability. The cropping strategies included continuous ryegrass/red clover (continuous grass), corn (Zea mays L.) harvested early followed by winter wheat (corn-wwheat-grass), corn followed by spring wheat (corn-swheat-grass), ryegrass/red clover rotated with winter wheat (grass-wwheat-grass), ryegrass/red clover in rotation with spring wheat (grass-swheat-grass), soybean [Glycine max (L.) Merr.] rotated by both winter wheat (soybean-wwheat-grass) and spring wheat (soybean- swheat-grass), corn double cropped (corn-corn-grass) and soybean followed by corn (soybean- corn-grass). Wheat was harvested as a cash crop in all simulated years and sold at a premium price. All rotations were in long rotation with perennial ryegrass/red clover (Lolium perenne / Trifolium pratense) over the 3-yr. In general, there was no economic and environmental benefit to shifting land from continues grass-based production to specified cropping rotations. However, under crop rotation, use of winter wheat should be encouraged, particularly soybean replaced with cash crop wheat, to reduce environmental impact and improve farm profitability.

O mercado de trigo (Triticum aestivum L.) orgânico para produção de pão cresceu em grande magnitude na região da Nova Inglaterra, nos Estados Unidos. Este nicho de mercado representa uma alternativa de renda para os produtores de leite orgânico abastecerem este mercado através do cultivo e colheita de grãos em rotação de cultura na própria fazenda. Objetivou-se com este estudo determinar a sustentabilidade de oito sequências de rotação de cultura (três anos de rotação) durante o período de 25 anos em uma propriedade produtora de leite orgânica bem manejada. Uma fazenda média foi simulada utilizando o modelo computacional Integrated Farm System Model (versão 3.6) para avaliar o efeito da rotação de cultura no desempenho da cultura, impacto ambiental e rentabilidade. As estratégias de rotação incluíram pasto contínuo (azevém e trigo), milho (Zea mays L.) colhido cedo seguido de trigo de inverno (milho-trigo de inverno- pasto), milho seguido de trigo de primavera (milho-trigo de primavera-pasto), pasto em rotação com trigo de inverno (azevém/trigo - trigo de inverno - azevém/trigo), pasto em rotação com trigo de primavera (azevém/trigo - trigo de primavera - azevém/trigo), soja [Glycine max (L.) Merr.] em rotação por trigo de inverno (soja - trigo de inverno - azevém/trigo) e primavera (soja - trigo de primavera - azevém/trigo), milho em cultivo consecutivo (milho - milho - azevém/trigo) e soja seguida de milho (soja - milho - azevém/trigo). O trigo foi colhido em grão e comercializado a preço premium em todos os anos simulados. Em todas as simulações foram cultivados azevém e trigo (Lolium perenne / Trifolium pratense) consorciados no terceiro ano. Em geral, não houve benefício econômico e ambiental na rotação de cultura em comparação o pasto contínuo (monocultivo). Entretanto, entre as rotações de cultura, o cultivo de trigo de inverno deve ser incentivado, particularmente em rotação com a soja, para reduzir o impacto ambiental e aumentar rentabilidade da fazenda.
Análise de ciclo de vida na avaliação de diferentes rotações de culturas com trigo em fazendas produtoras de leite orgânico
Keywords: Trigo; Triticum aestivum; Alimentos naturais; Leite - Produção; Agricultura orgânica; Sustentabilidade; Avaliação de Alimentos para Animais